Effects of Small-Sided Games Training Program on VO2 max and Football Playing Skills - Ary Suud Cahyo Alben; Devi Tirtawirya; Theophile Niyonsaba (Budapest International Research and Critics University, 2022)
Skills disparity in controlling the ball in the soccer pitch are skills that must be constantly improved and owned by every soccer player along with the ideal capacity of oxygen consumption known as VO2max. The small-sided game's training is all about needed. The aim is to reveal the extent to which is the effect of this latter program on VO2max and skills improvement. This study was a quantitative quasi-experimental research of 24 participants as a sample size from SSB schools in Yogyakarta. The instruments used were pretraining and post-training tests designed and implemented by the research after going through validation processes. The data obtained consists of mean, standard deviation based on some antropometric factors along with ANOVA data testing to view the means difference between/within unrelated groups for correlational calculations. Our results were impressive that significant effects were found either on VO2 max increment or players' performances. We concluded that the introduced program has beneficial impacts on our young soccer players related, specific performance, and VO2max indeed. On p-value < 0.05. We have realized that the substantial portion of correlated data has sig-value less than 0.05; that means strong effect was found. Shortly, soccer coaches, practitioners should always strive to incorporate deliberate training programs for the sake of their career and novice players.